A RENEWED CALL TO INTERRELIGIOUS DIALOGUE - Kalliath , Antony (Journal of Dharma, 2002)
While editing this number of Dharma on "A Renewed Call to Interreligious Dialogue" Ahmedabad where Mahatama Gandhi’s Sabarmathi Ashram exists, is still witnessing the pogrom against the Muslims. The ongoing macabre death dance in the name of religion has knocked India off the moral high ground it claims with regard to religious harmony and tolerance. The terrorist attacks on the World Trade Centre (Sept 11,2001), and on the Indian parliament (Dec 13, 2001), and the recent Sabarrnati Express massacre (Feb 27, 2002) and the ongoing unabated slaughter of Muslims in the various parts of Gujarath have thrown a spanner into the ongoing movements of inter-religious dialogues. Ayodhya is plunging India into a searing crisis that has the potency to tore the polity at the seams in the coming years if it is not contained to the satisfaction of minorities.